Feedback as an opportunity to promote lifelong learning in pre-service teachers: a mixed methods study - Matsumoto-Royo, Kiomi; Conget, Paulette; Ramírez-Montoya, Maria Soledad (Frontiers in Education, 2023)
The aim of this study was to investigate whether, within a practice-based curriculum, feedback on the assessment tasks provided during campus coursework offers opportunities to promote lifelong learning dispositions in pre-service teachers. For this, pre-service teachers (n=231) completed a validated questionnaire regarding lifelong learning dispositions. Then, feedback from assessment tasks (n=14) was analyzed to identify claims related to curiosity, motivation, perseverance, and self-regulation of learning. Finally, in-depth interviews were conducted with pre-service teachers (n=8) to explore their perspectives on feedback and lifelong learning dispositions. Data triangulation was used to confirm and add depth to the findings. Feedback on assessment tasks provided during campus course work promotes lifelong learning dispositions when: i) tied to authentic tasks, ii) is provide not only by teacher educators but also by peers, iii) incorporates both positive and negative comments, along with practical advice. The implication of findings for teacher education is discussed.